The crystal structure of cyanotrichite - Mills, Stuart J. (2015)
We report the single-crystal average structure of cyanotrichite, Cu4Al2[SO4](OH)12(H2O)2, from the Maid of Sunshine mine, Arizona, USA. Cyanotrichite crystallizes in space group C2/m, with the unit-cell parameters a = 12.625(3), b = 2.8950(6), c = 10.153(2) Å and β = 92.17(3)o. All non-hydrogen atoms were located and refined to R 1 = 0.0394 for all 584 observed reflections [F o > 4σF o] and 0.0424 for all 622 unique reflections. The cyanotrichite structure consists of a principal building unit of a three-wide [Cu2Al(OH)6] ribbon of edge-sharing Cu and Al polyhedra || b, similar to that found for camerolaite. The ribbons lie in layers || (001) and between these layers, while SO4 tetrahedra and H2O molecules form rods running || b. A hydrogen-bonding scheme is also proposed. A sample of cyanotrichite from the Cap Garonne mine, Le Pradet, France, showed a 4b superstructure with the following unit cell: space group P2/m, a = 12.611(2) Å, b = 11.584(16) = 4 × 2.896(4) Å, c = 10.190(1) Å and β = 92.29(6)o. The supercell could not be refined in detail, but nevertheless imposes constraints on the local structure in that while the space-group symmetry prevents full order of SO4 and H2O in the 4b supercell, it requires that the sequence of species along any given rod is [-SO4-SO4-(H2O)2-(H2O)2-] rather than [-SO4-(H2O)2-SO4-(H2O)2-].